Revitalisasi Situs Sejarah dan Kepurbakalaan sebagai Sarana Pembelajaran di Desa Hulung Kecamatan Taniwel Kabupaten Seram Bagian Barat - Touwe, Sem; Ufie, Agustinus; Pattiasina, Johan (Jurnal Pengabdian Arumbai, 2024)
The revitalization program of historical and archaeological sites in Hulung Village, Taniwel District, aims to utilize historical sites as interactive learning tools. This program involved students, teachers, and local communities using an experiential learning approach to enhance historical understanding and cultural preservation awareness. Activities like scavenger hunts and storytelling engaged students directly on-site, increasing their learning interest and participation. Program evaluation showed significant improvement in students' historical knowledge and teachers’ motivation to adopt more interactive teaching methods. Additionally, the local community benefited economically from the revitalization, opening new opportunities in educational tourism. This program demonstrates that experience-based approaches can create sustainable impacts on education and cultural preservation